Electrochemical ion transfer across liquid/liquid interfaces confined within solid-state micropore arrays – simulations and experiments - Strutwolf, J.; Scanlon, M.; Arrigan, Damien (Royal Society of Chemistry, 2009)
Miniaturised liquid/liquid interfaces provide benefits for bioanalytical detection with electrochemicalmethods. In this work, microporous silicon membranes which can be used for interface miniaturisationwere characterized by simulations and experiments. The microporous membranes possessed hexagonalarrays of pores with radii between 10 and 25 mm, a pore depth of 100 mm and pore centre-to-centreseparations between 99 and 986 mm. Cyclic voltammetry was used to monitor ion transfer across arraysof micro-interfaces between two immiscible electrolyte solutions (mITIES) formed at these membranes,with the organic phase present as an organogel. The results were compared to computationalsimulations taking into account mass transport by diffusion and encompassing diffusion to recessedinterfaces and overlapped diffusion zones. The simulation and experimental data were both consistentwith the situation where the location of the liquid/liquid (l/l) interface was on the aqueous side of thesilicon membrane and the pores were filled with the organic phase. While the current for the forwardpotential scan (transfer of the ion from the aqueous phase to the organic phase) was strongly dependenton the location of the l/l interface, the current peak during the reverse scan (transfer of the ion from theorganic phase to the aqueous phase) was influenced by the ratio of the transferring ion’s diffusioncoefficients in both phases. The diffusion coefficient of the transferring ion in the gelified organic phasewas ca. nine times smaller than in the aqueous phase. Asymmetric cyclic voltammogram shapes werecaused by the combined effect of non-symmetrical diffusion (spherical and linear) and by the inequalityof the diffusion coefficient in both phases. Overlapping diffusion zones were responsible for theobservation of current peaks instead of steady-state currents during the forward scan. Thecharacterisation of the diffusion behaviour is an important requirement for application of these siliconmembranes in electroanalytical chemistry.